Characterization of spectral and geochemical variability within the Ferrar Dolerite of the McMurdo Dry Valleys, Antarctica: weathering, alteration, and magmatic processes. Issue 1 (9th May 2013) - Salvatore, M.R.; Mustard, J.F.; Head, J.W.; Marchant, D.R.; Wyatt, M.B.
Abstract: Orbital spectroscopy and laboratory analyses are utilized to identify major geochemical variations throughout the Ferrar Dolerite exposed in the McMurdo Dry Valleys (MDV) of Antarctica. Our laboratory results highlight the range of primary and secondary chemical and spectral variations observed throughout the dolerite, and provide the necessary calibration for detailed orbital investigations. Pure dolerite units are identified and analysed throughout the MDV using Advanced Land Imager (ALI) and Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) orbital datasets. In conjunction with our laboratory analyses, orbital analyses indicate that the dolerite sills are dominated by MgO concentrations of c. 6–7 wt% except where influenced by orthopyroxene-laden magmatic injections, where MgO concentrations can reach as high as 32.5 wt%. ASTER analyses also indicate that spectrally significant alteration is limited primarily to surfaces dominated by fine-grained dolerites, which form and preserve well developed alteration rinds due to their resistance to physical erosion. The archetype of these secondary signatures is Beacon Valley, where a combination of cold, dry, and stable environmental conditions and the presence of fine-grained dolerites results in strong alteration signatures. This work provides unprecedented spatial coverage of meso- and macro-scale geochemical features that, until now, have only been identified in field and laboratory investigations.